Pelatihan Pengolahan Wortel sebagai Bahan Dasar Pembuatan Donat bagi Masyarakat Desa Situnggaling - Al Hilalwi Anwar Tanjung; Annisa Aulia; Resta Gunawan Hasibuan; Siti Nurmala (Lembaga Pengembangan Kinerja Dosen, 2025)
Carrots (Daucus carota L.) are horticultural plants with high nutritional content and abundant availability in the highlands of Karo Regency. However, its use at the community level is still limited to the sale of raw materials, so the economic added value is relatively low. This community service activity aims to improve the skills of the residents of Situnggaling Village in processing carrots into donuts with nutritional and economic value. The approach of the activity includes observation, interviews, socialization, and hands-on practice of making carrot donuts. The results showed a significant increase in the ability of residents to process agricultural products into food products with selling value, as well as the emergence of small groups that took the initiative to produce carrot donuts as a home business. This activity shows that training based on local potential is able to encourage economic independence and strengthen the spirit of entrepreneurship in rural areas. In addition, the innovation of processing carrots into creative products provides new opportunities in diversifying local food and increasing public awareness of the importance of optimal use of agricultural products. Through this activity, residents are expected to be able to develop products sustainably and expand marketing to increase family income.